Juan Gelman : vida y poesía Juan Gelman: life and poetry - Ortega Acevedo, Jorge Arturo (My University, 2020)
La muerte de Juan Gelman (1930-2014) puso a su hora el dedo en la llaga: ¿deben poesía y vida ser vasos comunicantes? / ABSTRAC The death of Juan Gelman (1930-2014) hit the nail on the head at the time: should poetry and life be communicating vessels?
El Septentrion
Keywords: Vida; Poesia; Lifetime; poetry; Campus Tijuana